Design and implementation of minichannel evaporator for electronics cooling - ÖZDEMİR, MEHMED RAFET (SPRINGER, 2021)
The present study elucidates the design and experimentation of a minichannel evaporator in an R134a vapour compression refrigeration system for electronics cooling applications. In the current study, a calculation module was developed to design a minichannel evaporator to keep the surface temperature of the chip below a certain value for reliable operation conditions in electronic cooling applications. In the calculation module, the conventional-scale heat transfer correlation was used to predict the surface temperature of the chip. On the other hand, the conventional-scale and microscale pressure drop correlations were tested to assess the pressure drop in the minichannel evaporator. The proposed calculation module was verified using experimental tests for different heat loads. It was found that the proposed calculation model predicted very well the experimental data of the surface temperature of the chip for all heat input. The calculation module with micro-scale pressure drop correlation predicted well the experimental pressure drop data in the minichannel evaporator for all heat loads. Moreover, the effects of the degree of subcooling, superheating degree and condensation temperature on the surface temperature of the chip and pressure drop in the minichannel evaporator were investigated to determine optimum operating conditions at different cooling capacities using the calculation module. The results showed that the increase in the degree of subcooling enhances the performance of the minichannel evaporator. On the other hand, the lower degree of superheating and condensation temperature yielded better performance for the minichannel evaporator. The feasibility of the results for electronic cooling applications is discussed based on the findings.
Keywords: Vapour compression refrigeration; Electronics cooling; Microchannel; Heat sink; HEAT-TRANSFER; 2-PHASE FLOW; REFRIGERATION SYSTEM; PRESSURE-DROP; WATER